The influence of personality on violent victimization – a study on police officers. Issue 6 (2nd July 2016) - Ellrich, Karoline; Baier, Dirk
ABSTRACT: The current study aims to examine the influence of police officer characteristics, civilian characteristics, and possible interactions between both on violent victimization of police officers. Based on literature distinguishing between 'provocative' and 'submissive' victims, focus is given on effects of police officers' personality in terms of the five-factor model plus risk-taking. Patrol police officers ( n = 1813) from Lower Saxony, Germany, completed a paper-and-pencil survey including personality assessments as well as questions about their last three police encounters. Binary logistic multilevel regression analyses demonstrate that police officers with higher scores on neuroticism and openness to experience were more likely to be violently attacked. Furthermore, agreeableness reduced police officers' risk of violent victimization, while risk-taking and neuroticism increased their risk when confronted with a violent civilian. The study indicates that personality and especially traits that are assumed to provoke potential perpetrators were linked with violent victimization. It further stresses the need to include perpetrator attributes in victim studies in order to identify relevant interaction effects between both parties.